2021
DOI: 10.1101/2021.10.21.465269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic analysis of intrinsic enhancer-promoter compatibility in the mouse genome

Abstract: Gene expression is in part controlled by cis-regulatory elements (CREs) such as enhancers and repressive elements. Anecdotal evidence has indicated that a CRE and a promoter need to be biochemically compatible for promoter regulation to occur, but this compatibility has remained poorly characterised in mammalian cells. We used high-throughput combinatorial reporter assays to test thousands of CRE - promoter pairs from three Mb-sized genomic regions in mouse cells. This revealed that CREs vary substantially in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 69 publications
(96 reference statements)
3
26
0
Order By: Relevance
“…To test these candidate elements in promoter-reporter gene assay, we first constructed a Luciferase plasmid that contained a 444 bp Trappc9 promoter fragment upstream of and including noncoding exon 1 (Figure 1C). The size of this promoter fragment is in line with standards from high-throughput testing of promoterenhancer interactions in the mouse genome (Martinez-Ara et al, 2022). We positioned the candidate regulatory elements downstream or upstream of the promoter-reporter gene cassette, depending on their relative locations within the Trappc9 locus (Figures 6A,B).…”
Section: Analysis Of Potential Gene Regulatory Regions Indicates Seve...mentioning
confidence: 65%
See 1 more Smart Citation
“…To test these candidate elements in promoter-reporter gene assay, we first constructed a Luciferase plasmid that contained a 444 bp Trappc9 promoter fragment upstream of and including noncoding exon 1 (Figure 1C). The size of this promoter fragment is in line with standards from high-throughput testing of promoterenhancer interactions in the mouse genome (Martinez-Ara et al, 2022). We positioned the candidate regulatory elements downstream or upstream of the promoter-reporter gene cassette, depending on their relative locations within the Trappc9 locus (Figures 6A,B).…”
Section: Analysis Of Potential Gene Regulatory Regions Indicates Seve...mentioning
confidence: 65%
“…However, there is currently no widely accepted consensus for a silencer chromatin signature and many silencer elements might be bifunctional elements acting through various mechanisms (Segert et al, 2021). Furthermore, a recent functional study of ENCODE3 candidate cis-regulatory elements (cCREs) found that the majority of annotated cCREs had no effect on transcription, while similar numbers of the remaining elements had enhancer or repressor activity, respectively, which was surprising given that cCREs are predicted to be enhancers (Martinez-Ara et al, 2022). Further experiments will be required to determine whether the silencer elements we identified within the Trappc9 locus might function in an allele-specific way and contribute to the brain-specific imprinted expression bias of this gene.…”
Section: Discussionmentioning
confidence: 99%
“…How the cell can make the correct decision to upregulate the correct gene is an important question for the future. One possibility is for instance promoter enhancer compatibility (Martinez-Ara et al, 2022), which is something that we cannot easily explore in our system.…”
Section: Open Chromatin Sites Are Highly Predictive For Gene Expressi...mentioning
confidence: 99%
“…This would mean that the distal downstream element drives 85% of expression and the proximal element a much smaller part of expression. Massively parallel reporter assays show that the both elements drive expression in roughly equal measure in an episomal context (Martinez-Ara et al, 2022). An alternative is the super-additive model in which multiple weak enhancers synergistically activate gene expression to a higher level than would be predicted from the sum of all enhancer activities.…”
Section: Open Chromatin Sites Are Highly Predictive For Gene Expressi...mentioning
confidence: 99%
“…Work in the Drosophila system suggested that many enhancers display high functional specificity for promoters with optimum expression requiring paired elements from either the developmental or housekeeping gene classes 22 . In contrast, recent work in human and mouse systems suggests that most enhancers can activate a wide range of core promoters and therefore display low specificity 23,24 . These later studies found that selectivity in enhancer activity at various core promoters is subtle and largely corresponds to matched enhancers and promoters from the same regulatory class.…”
Section: Introductionmentioning
confidence: 91%